Knowledge and practices among health functionaries working at first referral units: a cross sectional study in a district of Uttar Pradesh - Shukla, Brijesh Kumar; Kaushal, Suneel Kumar; Misra, Sunil Kumar Misra; Chaudhary, Shailendra Singh; Singh, Geetu (International Journal Of Community Medicine And Public Health, 2017)
Background: Pregnancy and child birth are normal event in the life of women. Most pregnancy results in normal birth but any pregnancy can develop complication at any stage so timely provision of obstetric services is extremely important and to the care by a skill birth attendant. So knowledge, skills and practices of these are very important. In light of above the study was carried out with objective to assess the knowledge and practices of medical officer and paramedical staffs (staff nurses and ANM) regarding antenatal services, intra-natal services, postnatal services. Methods: A cross sectional study was conducted at first referral units (FRUs) of Agra district of Uttar Pradesh, India from June 2015–August 2016. Structured open ended interview schedule were use d to collect the desired information. Before commencing the interview, informed written consent were taken from respondents. All medical officer and all staff nurse, public health nurse and auxiliary nurse midwives (ANM) were included as study subjects. Data were collected by first author himself. A total of 25 medical officers and 30 paramedical staff were interview for the study. Results: Almost all the medical staffs (100%) have knowledge regarding antenatal care except minimum ANC visit (80%) as practice of ANC services concerned less than half of them doing it as routine, nearly 1/3rd of medical staff (32.0%) conducted or assists delivery (i.e. only LSCS) in routine practices. Conclusions: Knowledge about maternal health services was more among medical staffs than paramedical staffs. Paramedical staffs have less knowledge as well as practice about neonatal resuscitation and infection control measure. Only less than 1/3rd of medical staffs conducting or assisting deliveries.